INNOVATIONS IN MEDICAL EDUCATION - Shakhman, Наталія; Mitiai, Мар’яна; Lysenko, Євген (Journal of Information Technologies in Education (ITE), 2021)
The article focuses on an innovative approach to the medical students’ education and training with the implementation of innovative technology of teaching mechanism. It also outlines the influence of the latest technology on students’ progress. The table of the virtual anatomical imaging system was used as an “innovative implementation” which became the driving force of the multimedia technology use.The effectiveness of using the virtual system on lectures was identified through regular testing to measure the students’ knowledge level of the studied material. The experiment involved only students of the medical faculty of Kherson State University, who specialize in medicine and are highly interested in getting practical skills as well as visualizing the study materials. The main component was a regular check of the students’ progress that was conducted in two groups taught with different teaching methods. The results demonstrate the continuous progress in the group, lectures were held using the interactive anatomical table. On the contrary,stability anda periodic decrease in the knowledge level were noted in the group, lectures were conducted without using the innovative technologies. The results of the experiment are presented in the form of a chart and a histogram that reflect the students' progress. It also studied the ability of students to conduct independent research work, the development of their intellectual abilities and creative potential. It should be emphasized the interactive anatomical table at Kherson State University covers several areas of application: medical universities and colleges, sports and medical facilities, television etc. The implementation of innovative technologies into the educational process requires the development and scientific substantiation of the content and methods of organization of the educational process that are mastered by the scientific and pedagogical staff of the medical faculty of the University.